Association of obesity indexes with dyslipidemia among adult residents in Shaanxi province: a cross-sectional survey - Rong LIU; Chenyue LIU; Rina SA; Yali TAO; Yanping Wang; Lin QIU (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo explore the associations of body mass index (BMI), waist circumference (WC), and waist to height ratio (WHtR) with dyslipidemia among adult residents in Shaanxi province for developing relevant intervention strategies. Methods Using stratified multistage random cluster sampling, we recruited 6 202 urban and rural permanent residents aged 18 years and above in 10 regions covered by national surveillance on chronic diseases and risk factors in Shaanxi province. Face-to-face interview with the questionnaire for China Adult Chronic Disease and Nutrition Surveillance - 2018, physical examination, and laboratory detections were conducted among the participants during May - November, 2018. Partial correlation analysis and unconditional multivariate logistic regression were adopted in analyses on the correlations of BMI, WC, and WHtR with the risk of dyslipidemia. ResultsDyslipidemia were detected in 1 994 (33.04%) of the 6 036 participants completing the survey. Laboratory detections revealed following results: (1) the mean levels (mmol/L) of the participants with underweight or normal weight/overweight/obesity were 4.56 ± 0.89/4.75 ± 0.95/4.79 ± 0.90 for total cholesterol (TC), 1.42 ± 0.99/1.80 ± 1.24/2.14 ± 1.39 for triglyceride (TG); 2.61 ± 0.78/2.79 ± 0.82/2.79 ± 0.81 for low-density lipoprotein cholesterol (LDL-C), and 1.45 ± 0.37/1.28 ± 0.32/1.17 ± 0.30 for high-density lipoprotein cholesterol (HDL-C); (2) the mean levels (mmol/L) of the participants with normal WC/mild central obesity/severe central obesity were 4.52 ± 0.90/4.73 ± 0.89/4.83 ± 0.98 for TC, 1.36 ± 0.96/1.76 ± 1.05/2.08 ± 1.57 for TG, 2.59 ± 0.77/ 2.77 ± 0.79/2.82 ± 0.86 for LDL-C, and 1.46 ± 0.37/1.31 ± 0.33/1.21 ± 0.31 for HDL-C; and (3) the mean levels (mmol/L) of the participants with normal WHtR/obesity were 4.46 ± 0.88/4.76 ± 0.92 for TC, 1.32 ± 0.95/1.83 ± 1.24 for TG, 2.55 ± 0.76/2.78 ± 0.81 for LDL-C, and 1.46 ± 0.37/ 1.29 ± 0.34 for HDL-C, respectively. There were significant differences in levels of TC, TG, HDL-C, and HDL-C among the participants with different BMI, WC, and WHtR (all P < 0.001). Partial correlation analysis showed that BMI, WC, and WHtR were correlated positively with TC, TG and LDL-C but negatively with HDL-C (all P < 0.001). After adjusting for gender, age, education, annual household income per capita, place of residence, smoking, and alcohol drinking, the results of multivariate logistic regression analysis demonstrated that the participants with overweight and obesity were at significantly higher risk of dyslipidemia, with the odds ratio (OR) (95% confidence interval [95%CI]) of 1.58 (1.36 - 1.82) and 2.22 (1.79 - 2.74) compared to the participants with underweight/normal weight; the results also showed that the risk of dyslipidemia was significantly higher for the participants with mild central obesity (OR = 1.49, 95%CI: 1.23 - 1.81) and severe central obesity (OR = 2.25, 95%CI: 1.79 - 2.83) in comparison with the participants with normal body weight; the dyslipidemia risk was significantly higher (OR = 1.39, 95%CI: 1.13 - 1.70) for the participants with the WHtR indicating obesity contrasting to the participants with normal WHtR. ConclusionThe prevalence of dyslipidemia was high among adult residents in Shaanxi province; the dyslipidemia prevalence was closely correlated with BMI, WC, and WHtR and increased with obese conditions.